(untitled) (Research, Society and Development, 2020)
The aim of the study was to understand how rural workers in Paty do Alferes deal with the risks of exposure to pesticides in tomato crops. To achieve this objective, a descriptive exploratory study with a quantitative approach was carried out. For data collection, a form was presented to workers from 02 tomato fields in that municipality, and data analysis was performed by calculating the relative frequency of responses. Fifty rural workers participated in the research, 100% male, 28% aged 36 to 40 years, 66% reported that they did not receive training for the pesticide work process, the rubber boot being the most used PPE reported by 30% of workers. Regarding the disposal of pesticide packaging, 36% of workers reported inadequate disposal, which leads to environmental contamination, bringing risk factors to illness. Regarding the storage of pesticides in the workplace, 40% of workers reported that it is stored in the packaging itself, but in the open. The study concludes that there is a poor understanding of the work process with pesticides in the municipality of Paty do Alferes where, as shown, workers have little understanding of the risks that this product brings to their health and the environment. Dealing precariously with your safety with the use of this product, presenting deficient strategies of attention to your health in face of the risks presented in the use of the pesticide.